Transformation of Communist Convictions in Young Intellectuals: Mlynář, Pelikán, Kosík, Kalivoda, Klíma, Kundera, Kohout, Vaculík - Hrubý, Karel (Dějiny – teorie – kritika, 2017)
This article attempts to elucidate the motivation, mentality, and attitudes of some of the young intellectuals, philosophers, writers, and political theorists who at first uncritically accepted Stalinist Communism, but in the course of the 1960s arrived at its critical re-evaluation. Their political convictions had changed, and these young people became involved in the cleansing process of the Prague Spring. At the same time, the author traces a change in their moral criteria, which took place especially after 1956. This article does not offer an analysis of their philosophical or artistic work, since that is subject to a different set of criteria. This contribution is methodically based on their personal testimonies about life guided by a dogma, which is confronted with their later views and values.